2015
DOI: 10.1039/c5en00093a
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticle toxicity and association with the alga Euglena gracilis

Abstract: Impact of silver nanoparticles (AgNP) on aquatic algae has largely been studied with model species that possess a rigid cell wall. Here we explored the interactions of AgNP with Euglena gracilis, a green alga having no cell wall but a pellicle. The toxicity and silver uptake upon 1-2 h exposures to various concentrations of AgNO3 and AgNP, having a mean size of 47 nm measured in the exposure medium, were examined. The photosynthetic yield decreased in a concentration-dependent manner and AgNP were less toxic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 36 publications
5
82
0
Order By: Relevance
“…More systematic studies are required to resolve the extent to which plant cell walls act as a barrier and for which NMs. Focusing on the interaction of Ag NMs with unicellular algae, Piccapietra et al () and Li et al () confirmed a strong interaction of particles with the cell surface of Chlamydomonas reinhardtii and Euglena gracilis , respectively, but with negligible uptake. The comparatively thick cell wall of algae appears to be a significant barrier to NM uptake.…”
Section: Cellular Mechanisms Of Toxicitymentioning
confidence: 98%
See 1 more Smart Citation
“…More systematic studies are required to resolve the extent to which plant cell walls act as a barrier and for which NMs. Focusing on the interaction of Ag NMs with unicellular algae, Piccapietra et al () and Li et al () confirmed a strong interaction of particles with the cell surface of Chlamydomonas reinhardtii and Euglena gracilis , respectively, but with negligible uptake. The comparatively thick cell wall of algae appears to be a significant barrier to NM uptake.…”
Section: Cellular Mechanisms Of Toxicitymentioning
confidence: 98%
“…Nano‐CuO sulfidation also occurs over several days with the initial formation of copper (I) sulfide (Cu 2 S) and possible transformation to CuS (Ma et al ). Unlike nano‐Ag and nano‐ZnO, the sulfidized form of the original nano‐CuO has greater solubility and releases more Cu 2+ than the parent NM (Ma et al ); as a consequence, the sulfidized form has been shown to be more toxic to aquatic biota (Li et al ).…”
Section: Environmental Fate and Behavior Of Nmsmentioning
confidence: 99%
“…Most of the literature has established that the biocidal activities of metallic nanomaterials are due to the dissolved metal ions (Aruoja et al, 2009;Li et al, 2015;Navarro et al, 2008;Wyszogrodzka et al, 2016), however, in some cases, direct contact between the organism and the material could be also responsible of the observed toxicity (Rodea-Palomares et al, 2011;Zhuang et al, 2012). To determine the contribution of dissolved metals to MOFs toxicity, MOF filtrates experiments were performed.…”
Section: Mofs Filtrate Bioassaysmentioning
confidence: 99%
“…[30] Previous report also showed that free nanoparticles could be toxic to plant and algae by strong sorption of nanoparticles onto the pellicle. [31] In the meantime, the shading of light absorption by QDs may lead to decreased light absorption by PSII, this may also contribute to the decreased photocurrent density. To avoid the toxicity and make effective use of QDs, CdTe QDs were first immobilized onto ITO substrates through the LbL assembly technique, which has been well developed by our group.…”
Section: Resultsmentioning
confidence: 99%